The Europeanization of Central and Eastern Europe - Madalina-Stefania Dirzu (CES Working Papers, 2011)
The Central and Eastern Europe Countries (CEECs) have been shaped by the EU conditionality, meaning that these countries were obliged to develop their administrative capacities in completely convergence with the acquis communautaire in order to join the European Union. The 2004 and 2007 enlargement of the EU and the accession negotiations have brought a systemic transformation of the CEECs through what is known in the literature as Europeanization. It seems to be a strong connection between conditionality and Europeanization, the former giving way to the latter. Therefore the capacity and the willingness of candidate countries to transfer the acquis into the domestic legal context have had a significant influence in the way in which the Europeanization process has succeeded in inhabiting the governance system of the CEECs. Considering these, the purpose of this paper is to examine through which mechanisms it was realized the correspondence between EU conditionality and the process of central and eastern enlargement-led Europeanization which seems to have been internalized distinctively by the CEECs, where administrative resources to comply with European standards were lagging behind.
Keywords: 330; Europeanization; conditionality; European Union; CEECs